Adaptive management in aid programmes (BEAM Exchange, 2014)
Aid works better – especially in complex and conflict-affected environ ments – when there is scope to trial and adapt programme strategies. S o argues Amir Allana in Navigating Complexity, a case study of Norther n Karamoja's Growth, Health and Governance (GHG) Programme that is ado pting an 'adaptive management' approach. This BEAM Exchange webinar in vited Amir, Tim Sparkman and Peter Roggekamp to discuss lessons from t heir work in Uganda and Cambodia. What does adaptive management look l ike in practice? And what does it require of managers and funders to m ake it happen? Tim and Peter share their experiences of applying adapt ive management techniques to the Growth, Health and Governance Program me and the Cambodia Agricultural Value Chain Program (CAVAC). Amir hig hlight insights from the Navigating Complexity report, including the i mportance of office culture, consistent management signals, and the ro le of supportive tools and processes.